REFORMASI SUMBER DAYA MANUSIA: KONSEP DAN STRATEGI PERUBAHAN UNTUK INDONESIA MAJU - Joko Tri Nugraha (Dialogue : Jurnal Ilmu Administrasi Publik, 2019)
Administrative reform in the developing countries becomes a necessity and focus of governments. The term administrative reform contains meanings, varied in functions, but also brings debate that has never been completed among practitioners, societies and theorists. Administrative reform aims to improve the performance of individuals, groups and institutions. One of the administrative reform agendas is to improve the salary of state apparatuses. However, the government does not have yet any payroll regulation of state apparatuses that relate their workload and proper reward. Consequently, its long-term impact is to bring down the spirit, work ethic and work discipline among the state apparatuses which are supposed to have high productivity and discipline. This article aims to explain the concept of administration reform from the perspective of human resources, as well as the change strategy for the development of Indonesia. It applied major theories of administrative reform and bureaucracy as well as human resource management. The method used is qualitative descriptive, with researchers as a tool based on literature studies. The results of this study show that administrative reform in the context of bureaucracy reform is not a new issue. Many ministries and institutions have implemented administrative reform, but not yet optimally gave positive results. The implications of this study is that bureaucracy reform should involve stakeholders in formulating performance indicators as well as the institutionalization of values and bureaucratic culture oriented towards the public interest.